Using of the Monte-Carlo simulation In the robust estimation for univariate A theoretical and experimental studys - Ganem, Adnan; Tayoub, Mahmoud (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يعد أسلوب محاكاة مونت – كارلو أسلوباً مهماً في مجال الحصانة ، لأنه يُمكن من دراسة سلوك العينات الصغيرة وتنبع أهمية أسلوب محاكاة مونت كارلو بشكل أساسي في إمكانية دراسة وتحليل كل من طرائق التقدير الحصين – وتقدير البيانات التي تشخص شواذاً لا سيما في حالة متغير واحد . وذلك انطلاقاً من استخدامه في توليد شواذ متماثل نظراً لدقته وكفاءته . - يشتمل هذا البحث عرضاً لبعض طرائق التقدير الحصين في مجال متغير واحد من خلال دراسة نظرية وتجريبية لمختلف المقدرات المعتمدة باستخدام أسلوب محاكاة مونت – كارلو . [1] The Monte-Carlo method of simulation is considered vital in the field of robust estimation simply because it enables in studying the behavior of small samples, and it’s importance emerges basically from the fact that it is possible to study and analyse both methods of robust estimation and to weigh data which pinpoint anomalous deviations especially in circumstances where univariates are employed. Such a procedure is accurate and efficient as long as it is used in generating identical. This research includes the explanation of some of the robust estimation methods used in conditions where univariates are used in the context of theoritical tical and pratical studies concerning divergent resources that follow the methods of Monte-Carlo simulation * أستاذ مساعد – قسم الإحصاء والتأمين – كلية التجارة والاقتصاد – جامعة صنعاء ص – ب : 13473 ** أستاذ مشارك – قسم الإحصاء والتأمين – كلية التجارة والاقتصاد – جامعة صنعاء ص - ب: 13473